MATING BEHAVIOR AND BREEDING OF THE BLUE TREE MONITOR, VARANUS MACRAEI IN AN IN-COUNTRY FACILITY IN INDONESIA: A PRELIMINARY NOTE - Beny Rahmanto; Evy Arida; Mochamad Arief Soendjoto (Treubia, 2022)
The Blue tree monitor, Varanus macraei Böhme & Jacobs, 2001 is a tree monitor species favored by reptile keepers. Successful captive breeding was reported from hobbyists and zoos in Europe shortly after its scientific description. Meanwhile, commercial farming to supply international demands has been progressing in Indonesia. However, such successful ex-situ breeding efforts have not yet been documented or published in Indonesia thus far. Therefore, in this, study we describe for the first time the mating behavior and reproduction of a V. macraei couple in an in-country outdoor facility, which is a common husbandry practice for monitor lizard breeders in Indonesia. The male started to approach the female at the beginning of the dry season, in May, with the female showing defensive behavior towards the male, both before mating and after laying eggs, pointing to a seasonal reproductive behavior. Monitor lizards were observed being active during the daytime. Eggs were laid by mid-July 2020. Two of the six eggs laid were revealed to be fertile and hatched after about 23 weeks (5.6 months). The two hatchlings were reared in an indoor enclosure, but only one survived, which showed to be a male.